Quantitative estimation of Atorvastatin calcium in bulk and tablet dosage forms using FTIR spectroscopy - PERIKA MOUNIKA; Y.PADMAVATHI; AKARI ANJALI; NAREDDY PREETHI REDDY (International Journal of Pharma and Bio Sciences, 2018)
Fourier Transform Infra Red (FTIR) spectrophotometric method was developed and validated for quantitation of atorvastatin calcium in bulk and tablet dosage forms. Active ingredients were extracted with methanol followed by chloroform. The method involves the measurement of absorbance of infra red band corresponding to N-H group centered at 3400cm-1 and evaluation of unknown drug component from the measured absorbance values using calibration plots. The developed method was validated according to ICH guidelines. The linearity of atorvastatin calcium was obtained in the concentration range of 10-50 μg/mL. Detection limits, precision and accuracy of the calibration curve were determined in order to validate the method. The mean recovery was found to be 100.37%. All the results were found to be within the limits and results were statistically compared with that of existing Ultraviolet(UV) method using t-test which indicated that there is no significant difference between two methods at p=0.05. From the results, it can be concluded that the proposed FTIR method was rapid, sensitive and economical for the quantitative estimation of atorvastatin calcium in bulk and tablet dosage forms